2015
DOI: 10.1155/2015/273968
|View full text |Cite
|
Sign up to set email alerts
|

Promotional Effect on Selective Catalytic Reduction of NOx with NH3 over Overloaded W and Ce on V2O5/TiO2 Catalysts

Abstract: W and Ce are known to be a good promoters to improve selective catalytic reduction (SCR) activity for V2O5/TiO2catalysts. This work aimed at finding the optimum ratio and loading of promoters (W and Ce) on V2O5/TiO2catalyst in order to improve SCR reactivity in low temperature region and to minimize N2O formation in high temperature region. In addition, we changed the order of impregnation between W and Ce precursors on V2O5/TiO2catalyst during the preparation and observed its effect on SCR activity and N2sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Vanadium oxide supported on anatase titania catalyst (VO x /TiO 2 ) is active for various reactions including selective oxidation or reduction. It has been well known as a conventional catalyst used in the selective catalytic reduction (SCR) process, which selectively reduces harmful NO x with NH 3 in lean conditions. Many studies have been performed to investigate structure–activity relationship in VO x /TiO 2 catalyst, where it is widely accepted that the degree of polymerization of vanadia on TiO 2 is a key factor that determines the activity or selectivity in the reaction. , …”
Section: Introductionmentioning
confidence: 99%
“…Vanadium oxide supported on anatase titania catalyst (VO x /TiO 2 ) is active for various reactions including selective oxidation or reduction. It has been well known as a conventional catalyst used in the selective catalytic reduction (SCR) process, which selectively reduces harmful NO x with NH 3 in lean conditions. Many studies have been performed to investigate structure–activity relationship in VO x /TiO 2 catalyst, where it is widely accepted that the degree of polymerization of vanadia on TiO 2 is a key factor that determines the activity or selectivity in the reaction. , …”
Section: Introductionmentioning
confidence: 99%
“…It can be seen in Figure 6 that the catalysts from BFS-TiO2 showed larger peak areas than that from commercial TiO2. As we all know, a catalyst possessing a larger reduction peak means the more reducible form of active species on the catalyst surface, which has a positive effect on NO catalytic reduction with NH3 [45]. These results demonstrated that the incorporation of SiO2 to BFS-TiO2 support is beneficial to disperse VOx and WOx species on the surface than pure TiO2 support did [12].…”
Section: Structure Of Prepared Supportsmentioning
confidence: 73%
“…These obvious differences in catalytic activity among the catalysts should be subject to different compositions, pore structures and acidic properties of used supports. The high surface area, surface acidity coupled with the more reducible form of VOx and WOx species on the surface of catalysts prepared from BFS-TiO2 supports allowed an enhancement of the catalytic efficiency in the SCR of NO by NH3 as compare to catalyst prepared from pure TiO2 [12,45]. The deNOx activity of slag-based catalysts increased with the increase of SiO2 content up to 9.2 wt.…”
Section: Catalytic Performance Of Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ammonia slip (i.e., unreacted NH 3 downstream of the SCR system) exceeding the need of the deNO x process can be minimized with an ammonia slip catalyst (ASC). Although that reduction of NH 3 can promote NO x and N 2 O formation [16], N 2 O may also be formed in lower concentrations through the SCR reactions [17,18]. Catalytic N 2 O reduction technologies are already available but are customized for other applications such as chemical industries and stationary combustion [19,20].…”
Section: Introductionmentioning
confidence: 99%